When Faculty Use Instructional Technologies: Using Clark's Delivery Model to Understand Gender Differences - Campbell, Katy; Varnhagen, Stanley (Canadian Journal of Higher Education, 2002)
Instructional and learning technologies are playing an increasingly important role in postsecondary education, but there is evidence that a number of differences exist in how females and males approach, perceive, and implement these technologies. As faculty start to offer more of their courses using flexible delivery methods such as Web-based conferencing, it is important to understand what gender differences may exist in faculty members' approaches to instructional and communications technologies so that this process may be better facilitated. This paper has three purposes: to highlight some of the major gender-related differences noted in the literature, including some from a feminist perspective; to present and discuss related findings found in an exploratory, post-hoc analysis of survey data collected from our institution; and finally, to suggest areas for future research. Richard Clark's (1994) model distinguishing between Instructional and Delivery Technologies provides a framework for this discussion.